White Spot Lesion Treatment Options: A Systematic Review of Different Techniques for Masking These Lesions - Michela Lamorgese; Nélio Veiga; Maria J. Correia; Ana T. P. C. Gomes; Sara Lopes; Lígia Lopes-Rocha; Rita Fidalgo-Pereira; Pedro C. Lopes (Gels)
White spot lesions (WSLs) are early clinical stages of enamel demineralization, often related to orthodontic treatment or poor oral hygiene. The use of gels such as fluoride for topical application inhibits demineralization and promotes remineralization of dental tissues through various mechanisms. A variety of therapeutic approaches are available; however, recent research indicates that combined treatment strategies may yield superior clinical outcomes compared to monotherapy. The aim of this study was to critically compare the efficacy of combining multiple treatment techniques for WSLs compared to using these techniques alone. A systematic search was conducted in PubMed, Scopus, and Cochrane databases according to PRISMA guidelines. The PICO strategy was used to formulate the research question: Which clinical approaches combined or isolated (C) influence the treatment and prevention effectiveness (O) of white spot lesions (I) in humans (P) in the last ten years (T)? Inclusion criteria focused on clinical studies from the last ten years evaluating the combined use of at least two treatment techniques for WSL, resulting in a total of 8 randomized controlled trials selected from an initial pool of 1185 articles. Our results suggest that combined treatment strategies, including resin infiltration with fluoride varnish and ozone therapy combined with fluoride application, demonstrated enhanced efficacy in lesion masking and remineralization compared to single-treatment approaches. CPP-ACP and hydroxyapatite-based creams improved aesthetics, particularly when used alongside fluoride varnish. Our study concluded that the combination of remineralization agents like fluoride gel, infiltrative resins, and antimicrobial treatments offers superior outcomes on white spot lesion treatment than using these techniques alone. However, long-term clinical studies are needed to standardize treatment protocols and confirm durability.